Indonesia Filsafat Bahasa dalam Kajian Pendidikan Islam: Indonesia - Roni Subhan; Alfiannisa Sawal Sugiharso; Septisa Tadzkia Aini (Yayasan Haiah Nusratul Islam, 2024)
Islamic education is an important aspect in forming a person's personality and spiritual understanding. In this context, philosophy of language plays a central role in understanding the nature of religious teachings and Islamic values. The study of philosophy of language is not limited to linguistic analysis, but also includes philosophical implications in the context of Islamic education.Understanding the philosophy of language allows you to delve deeper into the meaning of the verses of the Quran and Hadith and understand that language is the most important tool for communicating Islamic values.Therefore, the purpose of this article is to explain the relevance and contribution of language philosophy in the development of curriculum and teaching methods in Islamic education, thereby creating a deeper and more meaningful learning environment.